Peripheral inflammation is linked with emotion and mental health in people with obesity. A “head to toe” observational study - Amerikanou, Charalampia; Valsamidou, Evdokia; Kleftaki, Stamatia-Angeliki; Gioxari, Aristea; Koutoulogenis, Konstantinos; Aroutiounova, Maria; Stergiou, Ioannis; Kaliora, Andriana C. (Frontiers in Endocrinology, 2023)
Background Obesity is a significant worldwide health problem that is linked with mental health. The elucidation of the possible overlapping biochemical mechanism(s) involved in inflammation and oxidative stress is imperative to better understand and address obesity and related metabolic disorders. The aim of the study was to investigate the associations between inflammatory and oxidative stress profiles with parameters that reflect metabolic, emotional, and mental health in a Greek metabolically unhealthy obese cohort. Methods In total, 122 metabolically unhealthy people with obesity were recruited. Anthropometric measurements, biochemical, inflammatory and oxidative stress markers were assessed. Quality of life was evaluated through questionnaires for insomnia, self-esteem, depression, physical and mental health. Results The inflammatory biomarker tumor necrosis factor-alpha (TNF-α) and the ratio oxidized low-density lipoprotein/low-density lipoprotein (oxLDL/LDL) were higher in hypertensive (p=0.002, p=0.001 respectively) and hyperglycemic subjects (p=0.017, p=0.001 respectively). Furthermore TNF-α (p<0.001), oxLDL/LDL (p<0.001) and oxLDL/high-density lipoprotein (HDL) (p=0.016) increased significantly with the increase of metabolic syndrome components. Finally, a negative association between interleukin-6 (IL-6) and Rosenberg Self-Esteem Scale (Beta=-0.019, p=0.019) and a positive association between TNF-α and the Center for Epidemiologic Studies Depression Scale Revised (Beta=0.003, p=0.015) were found. Conclusions The results of the study suggest that obesity-related systemic inflammation is associated with worse self-esteem and depression symptoms, indicating an overlapping mechanism which can be utilized to the management of obesity.